ANTI OXIDANT EFFECT OF BETEL LEAF EXTRACT ON DRY - CURED FISH - KALAIMANI, N; MURALEEDHARAN, V; JOSEPH, K GEORGE; NAIR, T. S UNNIKRISHNAN (Fishery Technology, 2017)
The effect of betel leaf (Piper betle Linn.) extract on control of autoxidation of fat in dry fish has been studied. Oil sardine has been selected for experiments since it contains very high amount of fat. The treatments were given with 5% (w/v) betel leaf extract in water at different stages of salt curing. FF A, PV and TVN values of the samples were determined periodically to assess the keeping quality and autoxidation. The sample, prepared by dipping the fish in the extract immediately after salting and then drying as usual, was found to have better keeping qualities.